Cutaneous leishmaniasis in Iran: A systematic review and meta-analysis. (March 2021) - Sabzevari, Sadaf; Teshnizi, Saeed Hosseini; Shokri, Azar; Bahrami, Fariborz; Kouhestani, Fatemeh
Abstract: Cutaneous leishmaniasis as a public health concern that attracts many attentions in endemic area. There is no exact estimation of cutaneous leishmaniasis in Iran. This study aimed to assess the exact prevalence of disease and carried out in databases including: Pub Med, Google Scholar, Science Direct, Scopus, Web of Science, Magiran, Iran doc, Barakatkns and Scientific Information Database (SID) from 2000 to 2019. Totally 84 studies were eligible to be included in this systematic review and Meta-analysis study. Based on a random effect model the pooled prevalence of leishmaniasis was estimated 45% (95% CI: 39%–51%; I^2 = 99.8%P < 0.001). The highest prevalence of CL was related to Isfahan 66% (53%–78%), Golestan 64% (62%–65%) and Fars province 63% (38%–84%) and the lowest prevalence was estimated in Kermanshah province 4% (4%–5%), Hormozgan 10% (8%–11%), Bushehr 12% (1%–35%) and Kerman 15% (9%–22%) provinces respectively. The lowest prevalence was associated with L. trapica spices 23% (11%–38%) and the highest was associated with L. major spices 32% (21%–45%). The prevalence with both L. trapica and L. major spices was achieved 60% (48%–71%). It is essential for health authorities to take steps to control and prevent the epidemic by rapid treatment of patients, destroying gerbils and promotion of general and health education for the local population.